Employing; Health Awareness, Health Awareness Announcements: A research takenfrom a master’s degree thesis - Khalifa, Dhifaf Abd; Al-Amery, Muhammad Hassan (ALBAHITH ALALAMI, 2022)
The goal of health awareness is to familiarize people with health information and facts, and make them realize their sense of responsibility towards their health and the health of others.   And translate that goal in practice through applying healthy and sound behaviors spontaneously. This, the goal, is pursued by health awareness announcements through employing announcement persuasion of health as one of the methods of influencing the masses to adopt ideas, behaviors, and adherence to health advice and guidelines; The study aims to analyze the content of the Ministry of Health and Environment announcements regarding health awareness and to reveal the most employable persuasions in health awareness announcements. The researcher used the survey method that aims to record, analyze and interpret the phenomenon. The researcher used a content analysis tool to uncover the extent of employing persuasions in health awareness announcements.The researcher reached In its announcements, the Ministry of Health and Environment relied profoundly on persuading, as one advertisement included more than one appeal, and it relied in the first place on mental (scientific) persuasions in its various methods, such as citing information and facts, and building results on introductions to persuade the public and trigger a response.